An assessment of the perceptions of institutionalized Filipino youth - McCarthy, Maureen (1969)
It may well be that what we observe as delinquency and crime is more often than not recognized as a normal reaction of normal people to an abnormal condition. The juvenile delinquent is always a person whose spiritual, educational and/or social needs are not being met.
Includes bibliographical references.
Keywords: Juvenile delinquency -- Philippines -- Research; Young offenders -- Philippines -- Research; Delinquent behavior -- Philippines -- Research